Developing critical reading skills - Milan Spears, Deanne (1999)
Designed for reading courses at the intermediate and advanced level. As in past editions, this text continues to feature a wide range of interesting and diverse selections, excellent coverage of critical reading skills, and a concluding section on reading short stories. Using practice prose similar to the kind that students will encounter in the classroom, they are encouraged to analyze, interpret, question, and even challenge the words of the writer.